Nature and extent of histological changes induced by argon laser photocoagulation in canine gastric mucosa. Issue 12 (December 1980) - Kelly, D F; Bown, S G; Salmon, P R; Calder, B M; Pearson, H; Weaver, B M
Abstract : The tissue changes in canine gastric mucosa caused by exposure to an argon laser beam vary from mild mucosal oedema to complete cell destruction. Intermediate degrees of damage cause an inflammatory cell response with the formation of granulation tissue, particularly in the submucosa. The rate of healing is similar to that after other forms of injury to the gastric mucosa. Cell destruction at the surface of the mucosa starts with energies greater than 8 Joules on any one spot, and occurs at greater depths as the energy is increased but, unless cells are actually destroyed, the extent of histological damage is limited to a zone 1 mm lateral to, or below, the area exposed to the laser beam. Haemostasis is achieved by thermal contraction of bleeding vessels and of the surrounding tissue, thrombosis only occurring as a secondary effect.